2022
DOI: 10.3389/fmicb.2022.942603
|View full text |Cite
|
Sign up to set email alerts
|

Two new forest pathogens in Phaeolus (Polyporales, Basidiomycota) on Chinese coniferous trees were confirmed by molecular phylogeny

Abstract: Phaeolus schweinitzii (Fr.) Pat. was originally described in Europe and is considered a common forest pathogen on conifers in the Northern Hemisphere. Our molecular phylogeny based on samples from China, Europe, and North America confirms that P. schweinitzii is a species complex, including six taxa. P. schweinitzii sensu stricto has a distribution in Eurasia; the samples from Northeast and Southwest China are distantly related to P. schweinitzii sensu stricto, and two new species are described after morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Most of our new species in Phlebia s.l. were found in Yunnan Province, southwest China, a similar phenomenon was found in other groups of wood-rotting fungi [ 108 , 109 , 110 , 111 , 112 ]. The area is a hotspot for biodiversity, and more new taxa will be discovered after further investigations.…”
Section: Discussionsupporting
confidence: 81%
“…Most of our new species in Phlebia s.l. were found in Yunnan Province, southwest China, a similar phenomenon was found in other groups of wood-rotting fungi [ 108 , 109 , 110 , 111 , 112 ]. The area is a hotspot for biodiversity, and more new taxa will be discovered after further investigations.…”
Section: Discussionsupporting
confidence: 81%
“…The scientific names and their authors are mostly according to Index Fungorum ( https://www.indexfungorum.org/names/names.asp ) and MycoBank ( https://www.mycobank.org/ ). However, some updated scientific names are according to our recent studies (Cui et al 2019 ; Wu et al 2022 ; Yuan et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…was recorded as a common species in China (Dai 2012 ), but recent phylogenetic analyses found that five species were derived from Fomitopsis pinicola sensu lato, and Fomitopsis pinicola sensu stricto is distributed in Europe only. In addition, recent studies reported new pathogenic wood-rotting basidiomycetes from China (Wang and Dai 2022 ; Wu et al 2022 ; Yuan et al 2022 ; Zhao et al 2022 ). Furthermore, the systematics of wood-rotting basidiomycetes has changed with the advancement in molecular techniques, and many new genera have been established with numerous combinations proposed (Cui et al 2019 ; Sun et al 2019 , 2022 ; Wu et al 2022 ; Liu et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wood-rotting fungi as an important group within the Basidiomycota are known for their ecological role in the forest ecosystem in terms of decaying living and dead trees and recycling nutrients in forest ecosystems ( Dai et al., 2007 ; Yuan et al., 2021 ; Yuan et al., 2022 ). However, the diversity and taxonomy of these fungi remain not well known, and many new species have been described recently because of the application of molecular phylogeny ( Dai et al., 2021 ; Mao et al., 2023 ; Wang et al., 2021 ; Wang et al., 2022 ; Wu et al., 2022a ; Wu et al., 2022b ; Zhou et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A CTAB rapid plant genome extraction kit (Aidlab Biotechnologies, Co., Ltd., Beijing, China) was used to obtain DNA products from voucher specimens, according to the manufacturer’s instructions with some modifications ( Yuan et al., 2021 ; Yuan et al., 2022 ). The following primer pairs were used to amplify the DNA: ITS5 (5′-GGA AGT AAA AGT CGT AAC AAG G-3′) and ITS4 (5′-TCC TCC GCT TAT TGATAT GC-3′) for the internal transcribed spacer (ITS) regions ( White et al., 1990 ); LR0R (5′-ACC CGC TGA ACT 6 TAA GC-3′) and LR7 (5′-TAC TAC CAC CAA GAT CT-3′) for nuclear large subunit (nLSU) rDNA ( Vilgalys and Hester, 1990 ).…”
Section: Methodsmentioning
confidence: 99%